Rapidly Growing Pulmonary Metastasis from Anaplastic Meningioma with Lethal Outcome: A Case Report - Corniola, Marco V.; Landis, Basile N.; Migliorini, Denis; Lobrinus, Johannes A.; Ares, Carmen; Schaller, Karl; Jägersberg, Max (Journal of Neurological Surgery Reports, 2017)
Anaplastic meningioma is seldom encountered. Moreover, distant metastasis is extremely rare, with only a handful cases reported. Here, we report the case of a 74-year-old female patient who underwent a combined cranial and endonasal approach for an extensive spheno-orbital anaplastic meningioma (WHO grade III), followed by adjuvant radiotherapy. Although local tumor control was achieved, she presented with lung metastasis 2 years later. The patient then died from pulmonary complications related to chest metastasis.On the basis of this case, we discuss the available literature on metastatic meningiomas and radiologic follow-up strategies.
Keywords: anaplastic meningioma; endoscopic surgery; metastatic meningioma; skull base surgery; oncology